Upaya Peningkatan Pengetahuan tentang Efek Samping Obat pada Warga Dasa Wisma dalam Upaya Penerapan Farmakovigilans - Inayatush Sholihah; Joko Santoso (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
The lack of public understanding and awareness about safe drug information and misleading social media news related to drug use is a new challenge that cannot be underestimated. The purpose of this community service was to overcome the problem of the lack of public knowledge about side effects, especially as an effort to implement pharmacovigilance in the community. The method started from intervention to the community included providing education (socialization) on the dangers of drug side effects and workshops on the use of the method of measuring drug side effects using the Naranjo algorithm. The target of this activity was the residents of the Mertoudan, Mojosongo, Surakarta would get additional knowledge about drug side effects and know how to monitor it, also creating people who are aware of drug side effects. This activity increased the knowledge of residents about drug side effects and the ability to measure the probability of the occurrence of drug side effects. The implementation of this activity received a good response from the Chairperson of Dasa Wisma and the participants, who were very enthusiastic to increase their knowledge about drug side effects and the measurement method with the Naranjo algorithm.